Effects of constraint-induced movement therapy as a rehabilitation strategy for the affected upper limb of children with hemiparesis: systematic review of the literature - Nascimento,LR (2009)
BACKGROUND: Hand function impairment is the main disability among children with hemiplegic cerebral palsy. They start to perform most motor tasks exclusively with their unaffected upper limb, thereby causing a phenomenon described as learned nonuse. To minimize this phenomenon, constraint-induced movement therapy (CIMT) is emerging as a rehabilitation strategy for improving the functional use of the affected upper limb. OBJECTIVE: The aim of this study was to conduct a systematic review of the literature on the effects of CIMT among children with hemiparetic cerebral palsy. METHOD: This was a systematic review of the literature using randomized clinical trials to analyze the effects of CIMT on the functional performance of the affected upper limb among children with hemiparesis. RESULTS:Five studies fulfilled the inclusion criteria, and the methodological quality ranged from 2 to 6 (4.4±1.36), according to the PEDro scale. The studies included involved a total of 99 individuals who showed that CIMT had positive effects, compared with other rehabilitation strategies or no therapy. However, there was considerable variation between the studies regarding the measurement instruments used and the outcomes evaluated. CONCLUSION: Although the studies achieved positive results, it is difficult to draw any clear-cut conclusion regarding the effectiveness of CIMT because of the small number of studies and their methodological differences.